2021
DOI: 10.1089/aut.2020.0054
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Autistic Adults in Postsecondary Settings: A Systematic Review of Peer Mentorship Programs

Abstract: Background: The number of autistic individuals attending college or university is increasing, yet graduation rates are low as postsecondary environments often fail to support autistic students' individual needs. Peer mentorship programs are emerging as a promising approach for providing individualized, one-on-one support to meet this service gap for autistic postsecondary students. However, no literature has systematically described these programs. Methods: We conducted a systematic review that described exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 68 publications
(200 reference statements)
0
12
0
Order By: Relevance
“…This accessibility might be achieved by providing clear information in advance about social events, making sure events are in well-designed sensory spaces or using peer mentoring programs ( Cage et al, 2020 ; Scott and Sedgewick, 2021 ). Indeed, peer support programs for autistic students have shown promise ( Duerksen et al, 2021 ). Considering the high rates of considering dropping out, burnout, and mental health difficulties noted in this study – including how both groups qualitatively reported the negative impact the pandemic had had on their mental well-being – social support could be a crucial factor ( Mostert and Pienaar, 2020 ), which needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This accessibility might be achieved by providing clear information in advance about social events, making sure events are in well-designed sensory spaces or using peer mentoring programs ( Cage et al, 2020 ; Scott and Sedgewick, 2021 ). Indeed, peer support programs for autistic students have shown promise ( Duerksen et al, 2021 ). Considering the high rates of considering dropping out, burnout, and mental health difficulties noted in this study – including how both groups qualitatively reported the negative impact the pandemic had had on their mental well-being – social support could be a crucial factor ( Mostert and Pienaar, 2020 ), which needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative responses did not indicate any preference for particular formats or sources of support. Preliminary investigations could focus on summer transition programs, support groups, and peer or specialist mentoring as these can effectively support autistic students with the transition into university and their time at university (Knott and Taylor, 2014;Ames et al, 2015;Roberts and Birmingham, 2017;Siew et al, 2017;Lucas and James, 2018;Thompson et al, 2018;Hillier et al, 2019;Lei et al, 2019;Thompson et al, 2020;Duerksen et al, 2021). This approach would enable support to be more autism-specific, which our participants expressed a desire for.…”
Section: Discussionmentioning
confidence: 99%
“…Once at university, support can be substantial and wide ranging, including group (e.g., social clubs and peer support groups), as well as one-to-one support (e.g., mentoring; Anderson et al, 2017). Both peer and specialist mentoring (involving a one-to-one relationship between a professional mentor and student mentee) can effectively support autistic students with their academic and mental health needs during university (Knott and Taylor, 2014;Ames et al, 2015;Hillier et al, 2019;Duerksen et al, 2021), especially when there is a personalized approach underpinned by a strong mentor-mentee partnership (Roberts and Birmingham, 2017;Siew et al, 2017;Lucas and James, 2018;Thompson et al, 2018;Thompson et al, 2020).…”
Section: University Supportmentioning
confidence: 99%
“…Efforts to integrate peer helpers into the healthcare system are underway in several areas 18,19 . In autism, peer support interventions have been proposed in the school setting as a way to promote the development of social skills and academic engagement, rather than for the benefit of social support as such 20–23 . These programmes, mainly consist of neurotypical students offering support to autistic persons, rather than autistic persons supporting autistic persons.…”
Section: Introductionmentioning
confidence: 99%